Study of the Effect of Different Industrial Coating with Microscale Thickness on the CK45 Steel by Experimental and Finite Element Methods - Kashvzadeh, K.R.; Arghavan, A. (Проблемы прочности, 2013)
This article is aimed at analyzing the effects of
industrial coatings of hardened chromium, trim
chromium, hardened nickel and warm-galvanization
with a thin structure and dimensions in micron
scale, on fatigue endurance limit of
components. In order to do this, using the plating
process and the analyzed coatings with the
thickness of 13 and 19 m under the operation
conditions, the components of CK45 steel were
plated. An attempt was made to analyze the fatigue
of components by modeling the interface
phase between the base metal and coating more
accurately, using the linear spring elements. The
S–N curves obtained via the proposed finite element
model (including 3 different phases) and
other finite element models in which the shell element
was used to model the intermediate phase,
are compared to the experimental results. The
findings indicate that, considering the difference
between the S–N curves constructed via the present
finite element model and via test results, this
model is improved in comparison to the earlier
one, and yields more reliable results. Taking
into account the environmental and operating
conditions of components, the galvanized coating
is the most appropriate among low-thickness
coatings, but with significant increase in coating
thickness, the best choice becomes hardened
chromium coating. Increase in coating thickness
by 6 m reduces the fatigue limit by 14.96 and
4.37% for galvanized and hardened chromium
coatings, respectively. Анализируется влияние промышленных покрытий из упрочненного хрома, износостойкого хрома
и упрочненного никеля, полученных методом горячего цинкования, на предел выносливости
деталей. Предпринята попытка более точно проанализировать усталость деталей посредством моделирования границы раздела между основным металлом и покрытием, используя
при этом упругие элементы. Проведено сравнение кривых усталости, полученных представленным методом конечноэлементного моделирования (включая три различные фазы) и известными методами конечноэлементного моделирования, в которых для моделирования промежуточной фазы использовали элемент оболочки, с кривыми усталости, построенными по
данным экспериментальных исследований. Результаты показали, что данная модель является
усовершенствованной по сравнению с другими моделями и позволяет получить более надежные результаты. С учетом условий окружающей среды и эксплуатационных условий в качестве наиболее приемлемого покрытия представлено тонкое цинковое покрытие. При значительном увеличении толщины покрытия наилучшим вариантом является упрочненное хромовое покрытие. Увеличение толщины оцинкованных и упрочненных хромовых покрытий на 6 мкм
приводит к уменьшению значения предела выносливости на 14,96 и 4,37% соответственно. Аналізується вплив промислових покриттів із зміцненого хрому, зносостійкого хрому та зміцненого нікелю, отриманих методом гарячого цинкування,
на границю витривалості деталей. Зроблено спробу більш точно проаналізувати втому деталей за допомогою моделювання границі поділу між основним
металом і покриттям, використовуючи при цьому пружні елементи. Проведено порівняння кривих утоми, отриманих описаним методом скінченноелементного моделювання (включаючи три різних фази) і відомими методами скінченноелементного моделювання, в яких для моделювання проміжної фази використовували елемент оболонки, з кривими утоми, побудованими за даними експериментальних досліджень. Результати показали, що
дана модель є удосконаленою порівняно з іншими моделями і дозволяє
отримати більш надійні результати. З урахуванням умов оточуючого середовища й експлуатаційних умов як найбільш прийнятне покриття представлено тонке цинкове покриття. Зі значним збільшенням товщини покриття
найкращим є зміцнене хромове покриття. Зі збільшенням товщини оцинкованих і зміцнених хромових покриттів на 6 мкм значення границі витривалості зменшується на 14,96 і 4,37% відповідно.